Energy balance of the Earth’s tectonosphere - Gordienko, V. (Geofizicheskiy Zhurnal, 2015)
Concentration of K, U and Th has been investigated in the rocks of the Earth’s crust and upper mantle of platforms, geosynclines and oceans. The coinsidence has been found between total modern heat emanation in the crust and upper mantle of three types of regions with significant differences in the distribution of sources in depth. The values of upper mantle rocks radiogenic heat generation in these regions are about 0.04, 0.06 and 0.08 μW/m3 respectively. Correspondence of heat generation to geological history, heat flow and deep temperatures has been set for platforms. Implementation of energy conservation law in geological processes has been proven.